RESEARCH OF MOISTURE MIGRATION DURING PARTIAL FREEZING OF GROUND BEEF - V. M. Stefanovskiy; I. A. Polyakov; V. V. Petrov (Теория и практика переработки мяса)
The concept of «ideal product» is proposed for the study of mass transfer during partial freezing of food products by freezing plate. The ideal product is a product, in which number of factors affecting the «real product» (meat) are excluded. These factors include chemical composition of meat, quality grade of raw material (NOR, DFD, PSE), cryoscopic temperature that determines the degree of water transformation into ice, the phenomenon of osmosis, rate of freezing, etc. By using the concept of «ideal product» and its implementation in a physical experiment, it is proved that the “piston effect” causing the migration of moisture is due to frozen crust formation during partial freezing of the body. During partial freezing of the product by freezing plate, «ideal» and «real» food environment is transformed from closed system into open one with inflow of moisture to unfrozen part of the body. In the «ideal product», there is an expulsion of unfrozen moisture from freezing front, so the water appears on the body surface. Thus, the displacement of moisture increases by the same law, according to which the thickness (weight) of frozen layer increases. During partial freezing of ground meat, moisture does not appear on the surface of the product, but hydrates the unfrozen part of meat. The reason of this phenomenon is the expulsion of water during formation of frozen crust and water-binding capacity of meat.